Pengukuran Kecepatan Gelombang Seismik Menggunakan Metode Refraksi Pada Lapisan Tanah Dangkal - Admiral Musa Julius; Rian Mahendra Taruna; Shandy Yogaswara Surya Putra; Pande Komang Gede Arta Negara; Bryan Fitzgerald Amos Rumy; Alghani Yullatifah; Else Nopianti; Nurain Silvana Akuba; Taufan Taufik; Hendri Subakti; I Dewa Ketut Kerta Widana (Program Studi Pendidikan Geografi Universitas Hamzanwadi, 2020)
The strong and felt earthquake with magnitude 6.5 occurred in 119 km to the southeast of Cilacap Regency, Central Java Province at a depth of 48 km. The earthquake centered on the sea at coordinates 8.48o latitude and 109.17o east longitude on January 25, 2014. The earthquake triggered damage in several locations, including the districts of Banyumas, Kebumen, Cilacap and Purworejo. In order to mitigate natural hazards, this study aims to determine the relationship between seismic wave velocity and depth of layers near the surface in shallow geological structures. The method used in this study is the seismic refraction method. This method is done by interpreting seismic signals from man-made waves that spread near the surface of the earth. The seismogram will display the travel time of the waves, the distance between the waves and the source of the waves themselves. The structure of the geological layers that exist in the earth can be estimated based on the magnitude of the seismic wave velocity. This research is located in the campus area of the Indonesian Institute of Sciences Karangsambung. Measurements were made considering its location close to the center of the earthquake and the uniqueness of the rock formed by the removal of the ocean floor. Based on the results of the study it is known that there is a relationship between seismic wave velocity and the depth of the layers near the surface. The deeper the layer of soil from the earth's surface, the seismic wave velocity will be higher.